Antimicrobial Activity of Aloevera barbedensis, Daucus carota, Emblica officinalis, Honey and Punica granatum and Formulation of a Health Drink and Salad - Jeswin Philip; Sheila John; Priya Iyer (Malaysian Journal of Microbiology, 2012)
Aims: Indian folk medicine has been in practice from time immemorial. Traditional medicine interconnects our body with nature for a healthy living. The naturally occurring antimicrobials in food vary in their efficacy and function, toxicology, safety and mechanism of action against microorganisms.Methodology and Results: The study revitalizes the traditional system of medicine in order to achieve self reliance in health care and health for all by analyzing the antimicrobial property of aqueous extracts of aloevera (Aloevera barbedensis, carrot (Daucus carota, Indian gooseberry (Emblica officinalis, honey and pomegranate (Punicagranatum, and to assess the reason for inhibition of growth of pathogenic organisms by DNA and protein analysis. Various aqueous extracts showed inhibition to microrganisms like Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Shigella flexineri and Staphylococcus aureus.Conclusion significance and impact of study: The study also formulated and standardized a nourishing health drink and salad using the tested foods and estimated their shelf life and nutritive value. The health drink and salad had a low protein, low fat and moderate carbohydrate content. Therapeutically this drink and salad can be used to treat obesity.